Un modello informativo parametrico per il Duomo di Milano - Test e sperimentazioni - Lo Furno, Francesca; Pietrucci, Federica; Tommasi, Cinzia; Mandelli, Alessandro (Archeomatica, 2017)
Nowadays, with the spread of the BIM technology in the Cultural Heritage field, it is important to find, case by case, a method that permits to manage the archeological and architectural artifacts considering their personal needs. In this case, the project focuses on a portion of the roofs of the Milan Cathedral, chosen for the complexity and richness in shapes of the components, which leads to difficult survey operations. The target was to experience complex methods of multi-sensor and multi-scale data acquisition and to build an infographic three-dimensional reality-based model in order to help and manage the conservation activities of the building. The complexity of the Cathedral's late gothic style represents a hard challenge for the application of the innovative surveying methods and for modelling with a BIM-oriented software. For this reason, the experiment was made with two different modelling methods (one is object-oriented modelling BIM and the other is based on the use of NURBS surfaces), in order to find the differences between the two, in terms of managing the survey data, modelling, accuracy of the model, time required to create it and typology of data that they are able to visualize and insert. The result of this work is an example of methodological approach that can enhance the widespread application of this innovative technology for restoration or maintenance activities of built heritage.